Unravelling the identity of Pandora species (Bivalvia: Pandoridae) from Southern South America - Güller, Marina (2016)
Four species of Pandora have been reported from southern South America: P. cistula Gould, 1850, P. braziliensis G. B. Sowerby II, 1874, P. diffissa Mabille & Rochebrune, 1889 and P. patagonica (Dall, 1915). The group has received little taxonomic attention in this area, resulting in arbitrary and wrong usage of these names, for which several contradictory synonymies have been proposed. This study provides the first revision of Pandora species living in southern South America, including photographs of the type material and descriptions of shells, gross anatomy and living animals. Out of the four species previously mentioned, P. braziliensis is here regarded as valid, including P. patagonica and P. diffissa as synonyms. The fourth species, P. cistula, remains known only from its type specimen. In addition, a new species, P. brevirostris, is described from the shallow waters of Argentina.